Stages of development in Arabic philosophical nomenclature: emergence, progression and stability - Zaid, Tigani M. A; Zein, Ibrahim Mohamed (International Islamic University Malaysia, 2016)
The study of the creation of a technical language within an existing natural language reveals to us both the internal and external dynamics of this complex phenomenon. The history of Arabic lexical definitions of different disciplines in the historical Islamic civilization provides us with a wealth of information on how these processes take place at each level of development. In this article while we will be highlighting on the history of Arabic intellectual lexical definitions we will focus on the development of the disciplines that constitute the Arabic philosophical technical languages i.e. Kalām and falsafah. In each discipline we closely followed the three conventional phases of development i.e. emergence, progression and stability. It should be remarked that though there are distinctive features of each phase, yet there are equally overlaps among these phases. This study brought to our attention the significant place of al-Ta rifat of al-Jurjānī as the most sophisticated dictionary of sciences in the historical Islamic civilization.